Marriage and County-level Crime Rates: A Research Note. (February 2015) - Rocque, Michael; Posick, Chad; Barkan, Steven E.; Paternoster, Ray
Objectives: To determine whether the relationship between marriage and crime extends beyond the individual level of analysis by examining the relationship between marriage rates and crime rates at the county level. Methods: Linear regression analyses of marriage rates on various types of crime, including violent, property, drug, and juvenile crime arrest rates. Results: The analyses suggest that marriage rates are inversely related to rates of violent crime, property crime, drug use, and juvenile violence. Conclusions: This research note suggests that the relationship between marriage and crime is more far reaching than previous studies have indicated. Final remarks address the implications of the findings for theoretical work on crime causation and for public policy.